2018
DOI: 10.1186/s13046-018-0832-1
|View full text |Cite|
|
Sign up to set email alerts
|

Osteopontin alters DNA methylation through up-regulating DNMT1 and sensitizes CD133+/CD44+ cancer stem cells to 5 azacytidine in hepatocellular carcinoma

Abstract: BackgroundIn hepatocellular carcinoma (HCC), CD133+/CD44+ cells are one subgroup with high stemness and responsible for metastatic relapse and resistance to treatment. Our previous studies have demonstrated that osteopontin (OPN) plays critical roles in HCC metastasis. We further investigated the molecular mechanism underlying the role of OPN in regulating the stemness of HCC epigenetically and explored possible targeting strategy.MethodsCD133+/CD44+ subgroup sorting from HCC cell lines and HCC tissues was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…CA9 and PROM1 were also significantly overexpressed in Cluster2 even though these are not the most overexpressed genes (Table S7). Notably, SPP1 is one of the top upregulated genes in Cluster2 patients in both data sets ( Figure 7A, Tables S6 and S7), which was reported to enhance the stemness of HCC cells [19] and to be involved in PD-L1-mediated immune escape of HCC [20]. The characteristics of Cluster 2 identified by us is very similar to those of iCl1/C1 cluster, as reported by Woo et al [17].…”
Section: Identification Of Genomic Key Features In the Hcc Subtypessupporting
confidence: 82%
“…CA9 and PROM1 were also significantly overexpressed in Cluster2 even though these are not the most overexpressed genes (Table S7). Notably, SPP1 is one of the top upregulated genes in Cluster2 patients in both data sets ( Figure 7A, Tables S6 and S7), which was reported to enhance the stemness of HCC cells [19] and to be involved in PD-L1-mediated immune escape of HCC [20]. The characteristics of Cluster 2 identified by us is very similar to those of iCl1/C1 cluster, as reported by Woo et al [17].…”
Section: Identification Of Genomic Key Features In the Hcc Subtypessupporting
confidence: 82%
“…Recently, silencing tumor repressors or suppressive microRNAs in precancerous cells by epigenetic regulation has attracted increasing attention [31]. DNMT1 is abnormally activated in tumor tissues and cancer stem cells and functions by catalyzing DNA methylation [32,33]. In addition, DNMT1 is required for maintaining CSLC characteristics [33].…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 is abnormally activated in tumor tissues and cancer stem cells and functions by catalyzing DNA methylation [32,33]. In addition, DNMT1 is required for maintaining CSLC characteristics [33]. In breast cancer, epigenetic modifying agents, such as 5-azacytidine, could markedly reduce the CSC subpopulation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Since its overexpression is due to epigenetic regulation, using epigenetic modifier could be tested. It is widely demonstrated that epigenetic alterations are associated with different mechanisms of proliferation and metastasis in several types of cancer, including HCC [139,[161][162][163]. Histone acetylation is one of most important epigenetic mechanisms, regulating cellular events such as differentiation, proliferation, and cell cycle.…”
Section: Targeting Masmentioning
confidence: 99%